Species of Trichogramma parasitoid of Alabama argillacea I. Biology of three strains - Bleicher, Ervino; Parra, José Roberto P. (Pesquisa Agropecuaria Brasileira, 2014)
The biology of Trichogramma sp. (Piracicaba strain) andTrichogramma pretiosum Riley, 1879 (Iguatu and Goiânia strains) (Hym.: Trichogrammatidae), egg parasitoid ofAlabama argillacea (Hubner, 1818) (Lep.: Noctuidae), reared on Anagasta kuehniella (Zeller, 1879) (Lep.: Pyralidae) was studied under five constant temperatures (18°C, 20°C, 25°C, 30°C and 32°C). The duration of the egg-adult period for the three strains was significantly affected by the temperature, being the growth velocity increased with thermal elevation. The same species (T. pretiosum) reacted in a different way at lower temperatures according to its origin. The viability in the egg-adult period (for the three swains) was not affected by the temperature. The number of parasitoides emerged from a single egg of A. kuehniella was affected by temperature for Iguatu and Goiânia strains, Sexual ratio was not affected by temperature, although T. pretiosum showed a different one the two geographic locations. Temperature increase determined longevity reduction for both ted and not fed insects. It was observed that ted insects always had a shorter period of life. Insects from Iguatu and Piracicaba, when fed, showed a greater longevity at 20°C.